METHOD DEVELOPMENT AND VALIDATION OF VALACYCLOVIR HYDROCHLORIDE AND RITONAVIR IN TABLET DOSAGE FORM USING REVERSE PHASE HIGH PERFORMANCE LIQUID CHROMATOGRAPHY (Jurnal Teknologi (Sciences & Engineering), 2015)
Our main objective is to develop an accurate and precise RP-HPLC method for the simultaneous determination of Valacyclovir HCl and Ritonavir in tablet dosage form. An Agilent TC-C18 (2) column is used for the Separation of drugs by a mobile phase consisting of methanol, acetonitrile and water mixture in the ratio of 35:41.5:23.5v/v. The flow rate maintained was 1.3 mL/min and the wavelength used for detection was 222 nm. The linearity was observed in the range of 12.5-125µg/ml for Valacyclovir HCl (VC) and Ritonavir (RT) with a correlation coefficient of 0.9987 and 0.9981 respectively. The mean percentage recoveries for 80%, 100% and 120% accuracy were found to be 101.7%±2.09, 100%±2.49 and 101.5%±1.61 respectively for VC. The mean percentage recoveries for 80%, 100% and 120% accuracy were found to be 104.3%±0.99, 100%±1.77and 99.0%±1.22 respectively for RT. Linearity, accuracy, precision and robustness parameters for the suggested method were estimated for validation. The developed method can be utilized in the analysis of VC and RT tablets.